Morphology and microstructure of core-shell GaAs/GaxAl1-xAs nanowires investigated by He-ion microscopy and X-ray reciprocal space mapping. Issue 1707 (28th July 2014) - Re, Marilena; Di Benedetto, Francesca; Pesce, Emanuela; Miccoli, Ilio; Prete, Paola; Lovergine, Nicola; Tapfer, Leander
ABSTRACT: In this work we present new results on the morphological and microstructural properties of GaAs-Alx Ga1-x As (x≈0.24) core-shell nanowires (NWs) epitaxially grown on (111)B-GaAs substrates by Au-catalyst assisted metalorganic vapor phase epitaxy (MOVPE). Optimized growth conditions allowed us to fabricate highly-dense arrays of vertically-aligned (i.e., along the <111> crystallographic orientation) NWs. The NW arrays were investigated by Helium Ion microscopy (HeIM) and X-ray double- and triple-axis measurements and reciprocal space mapping (RSM). We demonstrate that these techniques can be employed in order to correlate some intrinsically local morphological information with statistically relevant (i.e. averaged over millions-to-billions of NWs) data on the NW structural properties.